Betty Crocker vegetarian cooking - Crocker, Betty (Hoboken, New Jersey : John Wiley & Sons, 2012)
"Updated third edition with information on how to fit vegetarianism into a busy lifestyle, how to feed vegetarian kids, and vegetarian myth busters"-- Provided by publisher.
"Vegetarian cooking isn't just for vegetarians anymore! Today, more and more families incorporate vegetarian meals and products into their everyday cooking. This updated third edition works for everyone - carnivore, flexitarian or dedicated vegetarian - with easy, family-pleasing recipes. Updated third edition with information on how to fit vegetarianism into a busy lifestyle, how to feed vegetarian kids, and vegetarian myth busters. Includes 180 meatless recipes for healthier eating with broad all-family appeal Complete nutritional analysis for every recipe Vegan recipes identified with an icon 60 beautiful full color photos throughout "-- Provided by publisher
1. Snacks, bites & nibbles -- 2. Grains, risotto & pasta -- 3. Gratins, casseroles & pot pies -- 4. Burgers, wraps & pizzas -- 5. Slow cooker -- 6. Soups, stews & chilies
Includes index
Keywords: Vegetarian cooking